Ig gene-like molecule CD31 plays a nonredundant role in the regulation of T-cell immunity and tolerance. - Ma,L; Mauro,C; Cornish,GH; Chai,JG; Coe,D; Fu,H; Patton,D; Okkenhaug,K; Franzoso,G; Dyson,J; Nourshargh,S; Marelli-Berg,FM (Proceedings of the National Academy of Sciences of USA, 2010)
CD31 is an Ig-like molecule expressed by leukocytes and endothelial cells with an established role in the regulation of leukocyte trafficking. Despite genetic deletion of CD31 being associated with exacerbation of T cell-mediated autoimmunity, the contribution of this molecule to T-cell responses is largely unknown. Here we report that tumor and allograft rejection are significantly enhanced in CD31-deficient mice, which are also resistant to tolerance induction. We propose that these effects are dependent on an as yet unrecognized role for CD31-mediated homophilic interactions between T cells and antigen-presenting cells (APCs) during priming. We show that loss of CD31 interactions leads to enhanced primary clonal expansion, increased killing capacity, and diminished regulatory functions by T cells. Immunomodulation by CD31 signals correlates with a partial inhibition of proximal T-cell receptor (TCR) signaling, specifically Zap-70 phosphorylation. However, CD31-deficient mice do not develop autoimmunity due to increased T-cell death following activation, and we show that CD31 triggering induces Erk-mediated prosurvival activity in T cells either in conjunction with TCR signaling or autonomously. We conclude that CD31 functions as a nonredundant comodulator of T-cell responses, which specializes in sizing the ensuing immune response by setting the threshold for T-cell activation and tolerance, while preventing memory T-cell death.